Foraging activity of Trachymyrmex fuscus (hymenoptera: formicidae) in a degraded area - Moreira, A. A.; Bueno, F. C. [UNESP]; Oliveira, C. G. [UNESP]; Diniz, E. A. [UNESP]; Garcez, D. L. [UNESP]; Campos, M. C G [UNESP]; Kato, L. M. [UNESP]; Bueno, O. C. [UNESP] (My University, 2007)
Two Trachymyrmex fuscus nests were observed between 2001 and 2002 in order to analyze the ant's foraging activity and the substrate collected by workers in an area modified by human activity. The analysis of results demonstrated alterations in the diel activity patterns of workers during the several months studied; however, we could not establish direct relations with variations in temperature and relative humidity. The materials transported to grow the symbiotic fungus were, for the most part, recently fallen or dry leaves, flowers, twigs, and seeds. The distances traveled by the ants until the foraging area and their collected material preferences revealed an opportunistic behavior, in which workers use plant parts according to the vegetation's phenology.
Keywords: Attini; Foraging behavior; Fungus-growing ants; Formicidae; Fungi; Hymenoptera; Trachymyrmex